Combination of biomarkers of vascular calcification and sTWEAK to predict cardiovascular events in chronic kidney disease - Bozic, Milica; Méndez Barbero, Nerea; Gutiérrez Muñoz, Carmen; Betriu, Angels; Egido, Jesús; Fernández, Elvira; Martín-Ventura, Jose L.; Valdivielso, Jose M.; Blanco Colio, Luis M. (Elsevier, 2018)
Background and aims Vascular calcification (VC) and atherosclerosis are associated with an increased cardiovascular morbimortality in chronic kidney disease (CKD). Osteoprotegerin (OPG) and osteopontin (OPN) are involved in both VC and CKD. Soluble tumor necrosis factor-like weak inducer of apoptosis (sTWEAK) has been related to cardiovascular disease. We hypothesized that OPG, OPN and sTWEAK levels may be associated with a higher prevalence of cardiovascular outcomes in patients with CKD. Methods The presence of calcified or non-calcified atherosclerotic plaques was assessed in 1043 stage 3 to 5D CKD patients from The NEFRONA Study. Biochemical measurements and OPG, OPN and sTWEAK serum levels were analyzed. Patients were followed for cardiovascular outcomes (41¿±¿16 months). Results At recruitment, 26% of CKD patients had VC. The adjusted odds ratios for having VC were 2.22 (1.32¿3.75); p=.003 for OPG, and 0.45 (0.24¿0.84); p=.01 for sTWEAK concentrations. After follow-up, 95 CV events occurred. In a Cox model, patients with OPG or OPN above and sTWEAK below their optimal cut-off points had an adjusted higher risk of cardiovascular events [HR: 2.10 (1.49¿3.90); p=.02; 1.65 (1.02¿2.65); p=.04; 2.05 (1.28¿3.29), p=.003; respectively]. When CKD patients were grouped according to the number of biomarkers above (OPG and OPN) or below (sTWEAK) their cut-off points, the combination of these biomarkers showed the highest risk for cardiovascular events [HR: 9.46 (3.80¿23.5) p¿<¿.001]. A composite score of these three biomarkers increased the C-statistic and net reclassification index beyond conventional risk factors and VC. Conclusions The combination of OPG, OPN and sTWEAK increased the predictability of cardiovascular outcomes.